Odpowiedzi

  • Eliz
  • Początkujący
2010-03-10T22:06:19+01:00
A) 2x+6=10
2x=4 /:2
x=2

b) 3x-3+2=8
3x=9 /:3
x=3

c)26-2x-9=1
2x=16 /:2
x=8

d)3-3x+2=-7
3x=12 /:3
x=4

e)3x+9=2x+8+x+1
3x+9=3x+9

f)12x+8+10x+15=-2x-13
24x=-36 /:24
x=-36/24

g)4x-8-2x+8=5x+5-3x
0=0

h)2x-8=4x-2+6x+6
-8x=12 /:(-8)
x=-12/8
3 4 3
Najlepsza Odpowiedź!
2010-03-10T22:22:32+01:00
A) 2(x+3) = 10
2x+6 = 10/(gadajaca kreska..nasz pani tak mowi) -6
2x = 4 / :2
x = 2
b) ) 3(x-1)+ 2 = 8
3x+3+2=8
3x+5= 8 /-5
3x=3/ 3
x=1
c) 2(13-x)-9 = 1
26+2x-9=1 /+9
26+2x=10/-26
2x= -16/ :2
x=-8
d) 3(1-x)+2= -7
3+3x+2= -7 / -5
3x = -12 / :3
x = -4
e) 3(x+3)= 2(x+4)+x+1
3x+9 = 2x+8+x+1
3x+9= 3x+9/ -9
3x=3x/ 3
0=0
3 2 3